Effect of endomentrial rceptivity on in vitro fertilization/intracytoplasmic sperm injection outcome in HUSM - Mohamadzon, Erinna (2018)
OBJECTIVE: To evaluate the association of endometrial receptivity by means of endometrial thickness, endometrial morphology and the level of serum progesterone with the outcome of in vitro fertilization/ intracytoplasmic sperm injection (IVF/ ICSI) cycles. STUDY METHOD: This prospective study was performed over a period of 18 months in Hospital USM Fertility Unit. A total of 50 patients going to receive IVF/ICSI cycles participated in the study. 50 subjects had undergone controlled ovarian hyperstimulation protocol until mature follicles were observed. On the day when the patient is to receive hCG injection, the endometrial thickness, endometrial morphology and the level of serum progesterone were determined. Oocyte retrieval was done which was followed by IVF or ICSI. The developed embryos were transferred into the uterus at blastocyst stage. Serum beta hCG was measured 14 days after embryo transfer. The association between endometrial thickness, endometrial morphology and level of serum progesterone with pregnancy was analyzed. RESULT: Pregnancy was achieved in 10 out of 50 patients (20.0%). The mean endometrial thickness for the pregnant group was 9.86 ±1.68 mm, whilst 9.77+ 2.53 mm in the non-pregnant group. 7 out of 10 pregnant patients had trilaminar endometrium. The mean progesterone level during the hCG day was 3.717 ± 1.071 nmol/L for the pregnant group and 1.408 ± 4.691 nmol/L for the non-pregnant group. All differences were not statistically significant. CONCLUSION: Endometrial thickness, endometrial morphology and the level of serum progesterone on the hCG day was not significantly associated with the outcome of IVF/ ICSI cycles. However, this finding was guarded by the small sample size.